INTERJEKSI DALAM FIKSI BERBAHASA INDONESIA - Eka Diana Pertiwi; Nusarini Nusarini (Universitas Sarjanawiyata Tamansiswa, 2018)
The objectives of this research are to describe (1) the attitude refers by interjection in Indonesian language fiction, (2) kinds of interjection in Indonesian language fiction, and (3) the distributions of interjection in Indonesian language fiction. This research was descriptive qualitative. The data in this research were paragraphs where was the sentences contained the elements of interjection in the Indonesian language. The data sources in this research were Intrik Sampe Elek Sampe Tuek novel by Redi Panuju in 2003, Humor Penangkal Sepi book by Safri H.S in 2009, Collection of short stories of Orang-orang Kotagede by Darwis Khundori in 2012, Jangan Bersedih novel by Eidelweis Almira in 2014, and Masa Lalu yang Tertinggal novel by Riri Anshar in 2014. The data collection used in this research was simak method with freely talk simak and take a note method. The data analysis method used agih method with balik and lesap techniques. The data presentation technique was informal method. The result of this research as follows: (1) the attitude referred to the interjection in Indonesian language fiction such as: negative attitude (underestimate). (2) the kinds of interjection in Indonesian language fiction such as: (a) invitation, (b) wonder, (c) surprise, (d) resentment / disappointment, (e) disgust, (f) relief, (g) calling / exclamation, (h) conclusion, and (i) gratitude. (3) the interjection distributives in Indonesian language fiction were in (a) beginning, (b) beginning and centre, and (c) beginning, center, and the end of the sentence.